Digital health literacy and sociodemographic factors among students in western Iran: a cross-sectional study - Fatemeh Darabi; Arash Ziapour; Hassan Ahmadinia (BMC Medical Education)
Abstract Introduction Digital health literacy is integral to accessing reliable information, especially for students making informed health decisions. This study aims to assess the digital health literacy level as well as sociodemographic factors of students of universities in Asadabad County, Hamadan, Western Iran. Methods The present research was a descriptive-cross-sectional study conducted between May to June 2024. The statistical population included 500 students from the following Iranian universities in Asadabad county: Islamic Azad University, Payame Noor University, Technical and Vocational College, and Asadabad School of Medical Sciences. The van der Vaart Digital Health Literacy Scale was used for data collection. Results The study showed that students’ digital health literacy status is moderate (47.19 ± 8.34). In the dimensions of digital health literacy, operational skills (61.84 ± 32.97) were at a desirable level, with the most significant issues related to privacy protection (23.51 ± 21.72). The mean digital health literacy score of students of Medical Sciences University was significantly higher than Azad University (P < 0.001) but lower than Technical and Vocational University (P = 0.048). There was a significant relationship between digital health literacy and the variables of the university of study (p < 0.001), gender (p = 0.049), education level (p = 0.017), nativity status (p = 0.001), and residence status (p < 0.001). Conclusion The results of the present study revealed that the digital health literacy of students in Iran was moderate, depending on sociodemographic factors. The findings from this study can be used to develop and implement interventions and strategies to improve digital health literacy.